CASES OF HARASSMENT AND ABUSE AGAINST WOMEN AND PROTECTION ORDER - Djamatov Mustafa Khatamovich; Rakhmonova Durdona Kilich kizi (Web of Journals Publishing, 2025)
The article focuses on the concept of harassment and abuse against women and girls, the causative factors, what kind of evidence a protection warrant is, and what restrictions can be placed on it.
Keywords: Harassment, abuse, victim of harassment and abuse, protection order.